Race and the totalitarian century : geopolitics in the Black literary imagination - Rasberry, Vaughn (London : Harvard University Press., 2016)
Few concepts evoke the twentieth century's record of total war, genocide, repression, and extremism more powerfully than the idea of totalitarianism: the ideological core of narratives of World War II and the Cold War. Yet the totalitarian experience, this book contends, shaped and was shaped by narratives of the rise and fall of the world color line. Extant works continue to confine the study of totalitarianism to Europe's collapse in World War II or to comparisons between the Soviet Union and Nazi Germany. Race and the Totalitarian Century parts ways with proponents and detractors of these normative conceptions to tell a strikingly different story. This story crystallizes in midcentury efforts by U.S. state actors to conscript Black Americans and their colonial counterparts into the global antitotalitarian struggle. For some critics, these efforts reoriented Black political actors around U.S. liberalism, or propelled them defiantly and misguidedly into the Communist sphere. By contrast, this book shows how an array of Black writers deflected, reimagined, and manipulated the appeals of liberalism and its antitotalitarian rhetoric in the service of decolonization. This skeptical view of the wartime opposition of totalitarian slavery and democratic freedom, the author argues, enabled writers like Richard Wright, W. E. B. Du Bois, Shirley Graham, C. L. R. James, and John A. Williams to formulate a powerful independent perspective from which to diagnose the convergence of the Cold War and the color line. Shedding new light on watersheds like the Bandung Conference of 1955 and the Suez Canal Crisis of 1956, this book develops a bird's-eye view of Black culture and politics that is at once an alternative history of the totalitarian century.--
Part One. Race and the totalitarian century -- The figure of the Negro soldier: racial democracy and world war -- Our totalitarian critics: desegregation, decolonization, and the Cold War -- In the twilight of empire: the Suez Canal Crisis of 1956 and the Black public sphere -- Part Two. How to build socialist modernity in the third world -- The right to fail: the communist hypothesis of W. E. B. Du Bois -- From Nkrumah's Ghana to Nasser's Egypt: Shirley Graham as partisan -- Bandung or barbarism: Richard Wright on terror in freedom -- Conclusion: memory and paranoia: John A. Williams's The man who cried I am.
Includes bibliographical references (pages 373-467) and index.
Keywords: African American authors -- Political activity -- History -- 20th century; African Americans -- Politics and government -- Philosophy; Totalitarianism and literature; Geopolitics in literature; Racism -- History -- 20th century; Politics and literature -- United States -- History -- 20th century